Diagnosis of 100 years old concrete from M. Lutoslawski Bridge in Lublin - Sławomir Karaś; Beata Klimek (Budownictwo i Architektura, 2014)
The paper presents the results investigation of old concrete. The material  was retrieved from M. Lutoslawski Bridge which is located in Zamojska Street. M. Lutoslawski built two bridges in Lublin  by using Francois Hennebique projects. The carried out investigations include recognition in situ and during laboratory tests. Among others, the concrete compression strength and  the diagnosis of concrete microstructure were made by means of SEM and EDS techniques. The conclusions pertain to both macro and microscopic analyses. The concrete strength results were compared with other authors' results obtained for similar old concretes.